2006
DOI: 10.1002/asia.200600232
|View full text |Cite
|
Sign up to set email alerts
|

Toward the Total Synthesis of Onchidin, a Cytotoxic Cyclic Depsipeptide from a Mollusc

Abstract: The total synthesis of onchidin (1), a cytotoxic, C2‐symmetric cyclic decadepsipeptide from a marine mollusc, according to the published structure, is described. A novel β‐amino acid, (2S,3S)‐3‐amino‐2‐methyl‐7‐octynoic acid (AMO), was efficiently prepared in high yield with high diastereo‐ and enantioselectivity based on a catalytic asymmetric three‐component Mannich‐type reaction with a chiral zirconium catalyst. The formation of sterically unfavorable N‐methyl amide and hindered ester bonds were successfull… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 36 publications
0
25
0
Order By: Relevance
“…150 In several of these cases, the lack of readily available authentic natural product sample precludes definitive structural revision, and therefore awaits re-isolation of the natural product or a close analogue. Total synthesis also revealed misassignment of the relative configurations for amphidinolide B2, 157 lituarines B and C from a sea pen, 158 marine fungal metabolite LL15G256γ, 159 and the molluscandepsipeptideonchidin 160 (Figure 4). Thus, total synthesis has been instrumental in the detection of marine natural product structural misassignments.…”
Section: Misassigned Marine Natural Product Structures Not Yet Revmentioning
confidence: 99%
“…150 In several of these cases, the lack of readily available authentic natural product sample precludes definitive structural revision, and therefore awaits re-isolation of the natural product or a close analogue. Total synthesis also revealed misassignment of the relative configurations for amphidinolide B2, 157 lituarines B and C from a sea pen, 158 marine fungal metabolite LL15G256γ, 159 and the molluscandepsipeptideonchidin 160 (Figure 4). Thus, total synthesis has been instrumental in the detection of marine natural product structural misassignments.…”
Section: Misassigned Marine Natural Product Structures Not Yet Revmentioning
confidence: 99%
“…The (2 S ,3 S )-configuration was also assigned to the Amoya unit in onchidin based on NOE studies and 1 H NMR coupling constant analysis; however, the total synthesis of onchidin suggested that a revision of the structure was necessary. 19 Therefore, it was planned to use Marfey’s analysis for assignment of the Amoya unit in companeramides A and B, facilitated by the availability of the synthetic 3( R )-amino-2( R,S )-methyloctanoate (Amo) standards. 20 …”
Section: Resultsmentioning
confidence: 99%
“…In addition, Kobayashi et al have developed enantioselective Mannich-type reaction of 5hexynal, 2-amino-m-cresol and a ketene silyl acetal derived from phenyl propionate by using an in situ generated chiral zirconium catalyst of (S)-6,6'-(C 2 F 5 ) 2 -BINOL. [147] As shown in Scheme 62, the process led to the formation of the corresponding Mannich adduct 246 in 85% yield, good synstereoselectivity (syn:anti = 91:9) in combination with excellent enantioselectivity of 96% ee for the major syn-product. Product 246 was further converted into onchidin, which is a natural cytotoxic, C 2symmetric cyclic decadepsipeptide.…”
Section: Multicomponent Reactions Based On the Mannich Reactionmentioning
confidence: 96%